If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + -8 = -1(2x + 7) Reorder the terms: -8 + -3x = -1(2x + 7) Reorder the terms: -8 + -3x = -1(7 + 2x) -8 + -3x = (7 * -1 + 2x * -1) -8 + -3x = (-7 + -2x) Solving -8 + -3x = -7 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -8 + -3x + 2x = -7 + -2x + 2x Combine like terms: -3x + 2x = -1x -8 + -1x = -7 + -2x + 2x Combine like terms: -2x + 2x = 0 -8 + -1x = -7 + 0 -8 + -1x = -7 Add '8' to each side of the equation. -8 + 8 + -1x = -7 + 8 Combine like terms: -8 + 8 = 0 0 + -1x = -7 + 8 -1x = -7 + 8 Combine like terms: -7 + 8 = 1 -1x = 1 Divide each side by '-1'. x = -1 Simplifying x = -1
| 3s+16=6+4s | | 3(5x+8)=-36 | | -40-5x+10x=45 | | x^2+18x+90=1 | | 3t+7=5t+9 | | 6x-91+12x=47 | | 30=18k | | -.33x-7=17 | | 16x^3(1-x)=0 | | 15(20x+1)-10x=115 | | r^2-r-2= | | 9x-62-2x=106 | | 40+2c=600 | | 5p+5-6=6p+3-24 | | 3x+11=57 | | .50x+4=8 | | 53=84-q | | -4(m+7)=-20-4m | | 1x+5=1x+6 | | 2(4x-3)=4x-72 | | 4x-3(x+1)=8x | | 2b-3=3b-9e | | 16x^3-12x^2-70x+36=0 | | 27y^3+x^3=0 | | 5(0.75x-1)=2x | | 41=7u-1 | | 2f-5g=-9 | | .25x+5=2 | | 20=5-3p | | 16b-65=9.5 | | i-8=23 | | 300+8p=20 |